Electron impact ionization mass spectra of some substituted dipyrido[1,2-a 4,3-d]pyrimidinones - Maki Esa; Pihlaja Kalevi; Huber Imre; Fülöp Ferenc; Bernáth Gábor; Vainiotalo Pirjo (1993)
The electron impact ionization mass spectra of dipyrido [1,2-a:4,3-d] pyrimidinones are strongly influenced by the degree of aromaticity of the fused rings. The molecular ions of the compounds are fairly stable. The main routes of fragmentation involve formation of the [M - H]+ ion and loss of substituents, H2CN., CO and alkyl radicals.
Keywords: Klinikai orvostan